2019
DOI: 10.1111/pre.12395
|View full text |Cite
|
Sign up to set email alerts
|

Japan's nationwide long‐term monitoring survey of seaweed communities known as the “Monitoring Sites 1000”: Ten‐year overview and future perspectives

Abstract: SUMMARY “Monitoring Sites 1000” – Japan's long‐term monitoring survey was established in 2003, based on the Japanese Government policy for the conservation of biodiversity. Ecological surveys have been conducted on various types of ecosystems at approximately 1000 sites in Japan for 15 years now and are planned to be carried out for 100 years. Since 2008, seaweed communities had been monitored at six sites, featuring the kelp (e.g. Saccharina and Ecklonia; Laminariales) and Sargassum (Fucales) communities in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 68 publications
0
28
0
2
Order By: Relevance
“…Despite the overlapping horizontal distribution of these species in Japan (Yoshida ; Terada et al . , ), their vertical distributions vary, which seems to be structured in response to the vertical attenuation of light. The relatively low compensation ( E c ) and saturation ( E k ) irradiances in the present study revealed the ability of S. macrocarpum to effectively photosynthesize under the low‐irradiance environment at the sublittoral depth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the overlapping horizontal distribution of these species in Japan (Yoshida ; Terada et al . , ), their vertical distributions vary, which seems to be structured in response to the vertical attenuation of light. The relatively low compensation ( E c ) and saturation ( E k ) irradiances in the present study revealed the ability of S. macrocarpum to effectively photosynthesize under the low‐irradiance environment at the sublittoral depth.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the limited distribution in East Asia, this alga is commonly found within temperate regions of Japan, including the coasts of Honshu, Shikoku, and Kyushu islands, which are particularly influenced by the warm Kuroshio and Tsushima currents (Yoshida ; Terada et al . ). This species is rarely found in subarctic Hokkaido Island and in the Pacific coast of northern Honshu Island (Pacific coast of Tohoku region) that is influenced by the cold Oyashio current (Kurile current; Yoshida ).…”
Section: Introductionmentioning
confidence: 97%
“…Murase et al 2000aMurase et al , 2000bYatsuya et al 2005), therefore providing important resources to the local fishing industry. Indeed, S. macrocarpum is one of the largest perennial brown seaweeds found throughout the Japan Sea Coast and the Seto Inland Sea of Japan (Yoshida 1983;Murase 2001;Terada et al 2019) and since Sargassacean species can be found in a variety of environments, such as exposed coastlines and quiescent bays, it is likely to exhibit superior tolerance to changes in environmental conditions (e.g. temperature and nutrient concentration).…”
Section: Introductionmentioning
confidence: 99%
“…The kelp Eisenia bicyclis (Kjellman) Setchell is one of the dominant species on temperate reefs around Japan (Kawai et al, 2020;Terada et al, 2020), and is one of the most phlorotanninrich kelp globally (Ragan and Glombitza, 1986). In the present study, two different experiments were conducted; experiment 1 tested the combined effects of warming, irradiance, and nutrient enrichment on maximum quantum yield of PSII (F v /F m ) to determine the irradiance and nutrient conditions in which warming induces photoinhibition in this kelp species.…”
Section: Introductionmentioning
confidence: 99%